The oncogenicity of tumor-derived mutant p53 is enhanced by the recruitment of PLK3 - Catherine A. Vaughan (Nature Portfolio, 2021)
The mechanisms of how gain-of-function (GOF) mutant p53 drives carcinogenesis are unclear. Here, the authors show that a GOF mutant p53 requires its transactivation capability to induce mouse lung tumors and this is dependent on PLK3 phosphorylation of GOF mutant p53.